2002
DOI: 10.1177/027507402237866
|View full text |Cite
|
Sign up to set email alerts
|

Public Versus Private Information Systems

Abstract: Citizens and policy makers have long made assumptions about differences between public and private organizations. Researchers have tested a variety of propositions concerning differences in public and private organizations (Rainey, Backoff, & Levine, 1976) based on a number of differences including environmental factors (e.g., higher degree of market exposure for private organizations), greater legal constraints and political influences for public organizations, organizationenvironment transactions (e.g., grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Not only firms have to provide services or products. Society requires firms transparency, efficiency and accountability [7,8] and besides protect the public interest. The commitment of public service organizations for the CSR issues is a key issue that must be analysed [25].…”
Section: The Relevance Of Csr In Soesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only firms have to provide services or products. Society requires firms transparency, efficiency and accountability [7,8] and besides protect the public interest. The commitment of public service organizations for the CSR issues is a key issue that must be analysed [25].…”
Section: The Relevance Of Csr In Soesmentioning
confidence: 99%
“…Governments are increasingly conscious of the relevance of applying concepts of CSR and therefore comply with criteria of efficiency and transparency [7,8]. Moreover, governments play an essential role in fostering and enhancing CSR and act as a public arbiter in this field [9] through the implementation of fiscal incentives or tax credits, by regulation and by creating rules to help society [9].…”
Section: Introductionmentioning
confidence: 99%
“…performance-based bonuses) which may not necessarily be provided to managers in public sector organizations [7]. Others have confirmed that private sector organizations invest more resources into ICTs compared to the public sector [47]. This is because the private sector views ICT as an important enabler for enhancing their competitive advantage which may not be as critical for public sector organizations given that they operate like a monopoly for most public services.…”
Section: Research Gapmentioning
confidence: 99%
“…According to Rocheleau and Wu (2002), the main difference between ITG in the public and private sectors lies in the fact that the public sector provides public goods and services, rather than services or products for sale. However, ITG in the public sector does not show significant conceptual differences from ITG in the private sector.…”
Section: Theoretical Frameworkmentioning
confidence: 99%